Latvia. Human Development Report 2010/2011: National identity, Mobility and Capability - (:unkn) unknown (Advanced Social and Political Research Institute (ASPRI) of University of Latvia, 2011)
The 2010/2011 report was produced under the auspices of the national research programme „National Identity”. The job of the report is to survey the content of individual national belonging in the context of human development. The report particularly focuses on emigration issues, because human development is weakened by a reduction in the size of the country’s population. The fact that people are moving to other countries shows that there is an endless competition among identities, as well as a transformation of those identities. The report also reveals the set of circumstances and techniques (the ability to act) which facilitate links between an individual and a location or region. The first two sections of the report review national identity and emigration, focusing more on problems and missions. The third section, however, studies abilities to act, making it possible to identify the achievements which various communities have ensured in terms of strengthening their sense of belonging to a specific location.
Keywords: National Identity; Migration; Regional Identity; Technical Information About the Survey Conducted Under the Auspices of the National Identity Programme